2022
DOI: 10.1021/acs.iecr.1c04111
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Local Flow Characteristics in a Gas–Liquid–Solid Circulating Fluidized Bed with Immersed Telocentric Photography

Abstract: The gas bubble size, local phase holdup, and other local flow characteristic parameters of the gas–liquid–solid circulating fluidized bed play an important role in the design and operation of this type of reactor. However, due to the limitation of measurement techniques of three-phase fluidization, the local flow characteristics have not been well measured and studied. In recent years, telecentric imaging technology has been applied in other multiphase systems, and a new telecentric probe method has been used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The positive effect of superficial gas velocity on G S is significant. This is qualitatively consistent with the findings of Zhang et al 19 on macroscopic three-phase circulating fluidized beds. Increasing the superficial gas velocity generates more voids near the gas injection point, reducing the local pressure at the bottom of the riser and creating a higher pressure drop between the downer and the riser.…”
Section: Bubble Velocitysupporting
confidence: 93%
See 4 more Smart Citations
“…The positive effect of superficial gas velocity on G S is significant. This is qualitatively consistent with the findings of Zhang et al 19 on macroscopic three-phase circulating fluidized beds. Increasing the superficial gas velocity generates more voids near the gas injection point, reducing the local pressure at the bottom of the riser and creating a higher pressure drop between the downer and the riser.…”
Section: Bubble Velocitysupporting
confidence: 93%
“…Regardless of the particle diameter, the bubble diameters expressed in the center of the interval follow a log-normal distribution, with a narrower size distribution for dispersed bubble flow regime and a broader distribution for coalesced bubble flow regime. Zhang et al 19 observed that the distribution of D b in a macroscopic circulating fluidized bed also follows a log-normal distribution. However, Li et al 5 found that the bubble sizes in a three-phase microexpanded bed with an inner diameter of 0.8 mm conform to normal and step distributions under dispersed bubble flow regime and coalesced bubble flow regime, respectively.…”
Section: Bubble Characteristics In the Circulating Fluidization Regim...mentioning
confidence: 99%
See 3 more Smart Citations